A biomechanical perspective for the kinematic analysis of robot manipulators - Carvalho, Alexandra M. S. F. (2016)
Mechanical manipulators are described through mathematical models based on the formalisms of the classical physics. The kinematic and dynamic models aloww the study of the phenomena involved , but ar complex to tackle at a design stage. as a consequence, present day robotic structures have porr performances when compared with the human arm. In fact, joint-driven manipulators ar not efficient tasks. Muscle-actuated arms are superior because the anatomic levers adapt the manipulating exigencies to the driving actuators, the kinematic analysis of these systems highlights its main properties and constitutes a step towards the design of new mechanical biological-like robotic structures.